Impact of topical cetylated fatty acid cream on hand osteoarthritis: a randomized, double-blind clinical trial - Sitthiphong Suwannaphisit; Nitiphoom Sinnathakorn; Pormes Suwanno; Warangkana Fongsri; Boonsin Tangtrakulwanich (Scientific Reports)
Abstract In addition to topical non-steroidal anti-inflammatory drugs that are used in hand osteoarthritis, there are other drugs that can reduce pain in osteoarthritis, such as topical cetylated fatty acids. Previous studies have reported that topical CFAs are effective in all knee OA patients, with slightly higher evidence for those with advanced disease. The mechanism of pain in OA knee and OA hand is similar. Furthermore, there are no previous studies on CFAs in OA hand. Patients fulfilling the American College of Rheumatology criteria for hand OA participated in this randomized, double-blind, placebo-controlled study. Eligible patients were over 40 years of age, had at least one tender joint, and had a joint pain visual analog score of 30–60 mm. Patients received topical CFA (n = 36) or placebo (n = 36) twice daily for six weeks. The primary outcome was the Functional Index for Hand Osteoarthritis (FIHOA) at 2, 4, and 6 weeks. The secondary outcome measures included the Visual Analog Score (VAS), Patient Global Assessment (PGA), and skin irritation at 2, 4, and 6 weeks. At baseline, no statistically significant differences were observed among the assessment parameters. Upon concluding the 6-week study period, it was evident that patients in the CFA group exhibited a notably lower mean pain score compared to those in the placebo group (2.2 ± 1.9 vs. 3.2 ± 2.2, P < 0.05) and achieved superior PGA scores (2.1 ± 1.7 vs. 3.1 ± 2.2, P < 0.05). However, no significant disparity was detected in terms of FIHOA between the two groups. Additionally, adverse reactions were reported by two patients in the placebo group, whereas no such reports were documented in the CFA group. Topical CFAs demonstrate efficacy in alleviating pain and enhancing patient global satisfaction in the treatment of hand osteoarthritis. However, a more extended follow-up period is imperative to ascertain whether disparities exist in the safety profile and functional outcomes between topical CFAs and a placebo.